Studying and Challenging Racism in Higher Education: Naming Bad Faith to Understand the "Logic" of Racism - Antar A. Tichavakunda (MDPI AG, 2021)
In this conceptual essay, the author argues that bad faith is a valuable concept in understanding and challenging racism in higher education. The philosopher Lewis Gordon argues that racism is a manifestation of bad faith. For the actor who sees Black people as less than human, for example, no evidence will allow the actor to see otherwise. Bad faith is the disavowal of any disconfirming evidence which allows actors to maintain their worldviews. The author draws from high profile examples of racism in higher education as conceptual cases to make his argument. Specifically, the author demonstrates how attacks upon Critical Race Theory in education, the currency of critiques of microaggressions research, and the perennial difficulty to name racist violence on campus as hate crimes operate upon a logic of racism through bad faith.